Motivation and Perception of Parental Support: A Study with Young Athletes of Individual and Team Sports - Silva, Fernanda Santos Calo [UNESP] (2022)
Parental support in relation to their children's sporting trajectory guides sporting development. This study aimed to analyze the perception of athletes about their parents' involvement and motivational orientation in relation to their participation in sports. A total of 319 athletes, aged between 7 and 18 years (13.3±2.73), from different sports, participated in the research. The instruments Parental Involvement Sport Questionnaire (PISQ) and Task and Ego Orientation in Sport Questionnaire (TEOSQ) were used. The results show that the athletes perceive parental participation most strongly in the dimension Directive Behavior (3.17±1.54). Active Involvement showed a mean score of (3.80±1.52), demonstrating that the participants consider their parents to «almost never» participate actively in the sports context. The data suggest that in team sports there is a greater perception of parental control over sporting behavior (p=0.015). Parental participation in team sports proved to be more active when compared to individual sports (p<0.001). In conclusion, the research points to the importance and influence that parental support, as well as the motivational guidance profile of athletes can have, in the segment, continuity, physical and emotional development, and even performance in sport.